Adolescent-parent conflict as preceived by the adolescent : a study of the development of independence in adolescence : a thesis presented in partial fulfilment for the degree of Master of Arts in Education - Chong, Helen (Massey University, 1975)
The development of independence is one of the major developmental tasks of adolescence. The development of two aspects of independence - economic independence and emotional independence - were considered in this study. It was postulated that when the individual is emotionally dependent on his parents, and acceptant of being so, the degree of conflict with parents is low and that during the period of striving for emotional independence the degree of conflict with parents rises to a maximum, then falls as emotional independence is established. After a consideration of factors stated in the literature to be related to adolescent-parent conflict the following hypothesis was developed and tested: for those adolescents living with their parents who are by law permitted to engage in full time employment there is an inverse relation between the degree of economic independence and the degree of conflict with parents, regardless of age, sex, socio-economic status and whether or not the adolescent is a student. A scale to measure degree of conflict was developed and used to assess degree of conflict with mother, with father, and with both parents together. From 133 responses to the questionnaire designed to test this hypothesis a sample of 85 Europeans, ranging in age from 15 to 19 years who came from families where both the natural parents were present was obtained. The hypothesis was not verified. Conflict with mother was found to decrease with age. No other factors were found to be related to degree of conflict. An analysis of the areas of conflict indicated, on average, a greater number of areas of conflict with mother than with father and a greater number of areas of conflict with father than with both parents together. Examination of the highest ranking areas indicated that adolescents argue more with their mothers about specific home-centered topics and more with their fathers and both parents together about abstract and external topics. This difference in the nature of adolescent-parent conflict was explained in terms of the structure of the New Zealand family and the role each parent plays in the family.
Keywords: Parent and child; Adolescence